Comparison of students' interests and learning outcomes through Google Sites on biodiversity materials - Tafari, Hairun; Pada, Andi Ulfa Tenri; M. Nur, Yaumil Istiqlal; Unzila, Fazia; Khairunnisa; Mhafhani, Arifah; Ruhmi (Jurnal Pendidikan Sosiologi dan Humaniora, 2026)
Teachers in schools currently use learning tools such as media, teaching materials, and LKPD, but these tools have not been able to increase students' interest and learning outcomes. One of the solutions to overcome this problem by using innovative learning tools is a Google Site-based learning tool. This research was conducted to determine the influence of Google Site-based learning tools on students' interests and learning outcomes. The method used is Quasi-Experiment with a quantitative approach, as well as with a non-equivalent control group type of research. Data were analyzed by t-test and Mann-Whitney test. Based on the data obtained, it shows that the data on learning interest is obtained with a value of Sig.= 0.88. The learning outcome data obtained a Sig.<0.001 value for the experimental class and the control class, while the N-Gain value was obtained with a Sig.=0.492 value. The results showed that the average learning interest of the experimental class was higher than that of the control class, but the difference was not statistically significant. The average N-Gain of the experimental class was also higher than that of the control class, but the results of the mann-Whitney test showed no significant difference between the two classes. Google Site-based learning has the potential to increase interest and learning outcomes, but it has not been significantly effective in this study.